Curcumin in the treatment of inflammation and oxidative stress responses in traumatic brain injury: a systematic review and meta-analysis - Guo, Jinfeng; Li, Zhengjie; Yao, Yun; Fang, Lei; Yu, Mingdi; Wang, Zuhui (Frontiers in Neurology, 2024)
Background and Aim: Traumatic brain injury (TBI), a leading cause of high morbidity and mortality, represents a significant global public health challenge. Currently, no effective treatment for TBI exists. Curcumin, an active compound extracted from the root of Curcuma longa, has demonstrated neuroprotective properties both in vitro and in vivo. Notably, it has shown potential in reducing oxidative stress and inflammation and enhancing redox balance. This paper conducts a systematic review and meta-analysis to explore curcumin's role in TBI animal models extensively. The findings offer valuable insights for future human clinical trials evaluating curcumin as a therapeutic supplement or nutraceutical in TBI management. Methods: Comprehensive literature searches were conducted across MEDLINE, Embase, Cochrane, Web of Science, and Google Scholar databases. These searches aimed to identify relevant manuscripts in all languages, utilizing the keywords "curcumin" and "traumatic brain injury." Results: The final quantitative analysis included 18 eligible articles corresponding to animal studies. The analysis revealed that curcumin significantly reduced inflammatory cytokines, including IL-1β (P=0.000), IL-6 (P=0.002), and TNF-α (P=0.000), across various concentrations, time points, and administration routes. Additionally, curcumin markedly enhanced the activity of oxidative stress markers such as SOD (P=0.000), Sir2 (P=0.000), GPx (P=0.000), and Nrf2 (P=0.000), while reducing MDA (P=0.000), 4-HNE (P=0.001), and oxyprotein levels (P=0.024). Furthermore, curcumin improved cerebral edema (P=0.000) and upregulated neuroprotective factors like synapsin I (P=0.019), BDNF (P=0.000), and CREB (P=0.000), without reducing mNSS (P=0.144). About autophagy and apoptosis, curcumin increased the activity of Beclin-1 (P=0.000) and Bcl-2 (P=0.000), while decreasing caspase-3 (P=0.000), the apoptosis index (P=0.000), and P62 (P=0.002). Conclusions: Curcumin supplementation positively affects traumatic brain injury (TBI) by alleviating oxidative stress and inflammatory responses and promoting neuroprotection. It holds potential as a therapeutic agent for human TBI. However, this conclusion necessitates further substantiation through high-quality literature and additional randomized controlled trials (RCTs).